Scoping Study : Leadership Development Programs/Models : Project, Building Leadership Capacity in Undergraduate Student. - Cohen, Lynne (Australian Learning and Teaching Council (ALTC), 2010)
Final report of a scoping study conducted as the first phase of a broader study funded by the Australian Learning and Teaching Council Fellowship (ALTC). The study sought to identify programs for leadership development for undergraduate students and to identify best practice models both in Australia and internationally. An environmental scan of university websites and the literature was conducted in order to build a data base of resources and to identify practitioners who can contribute to an ongoing dialogue and form a network of practitioners with expertise in leadership development. The models of leadership that emerged from the literature include the Social Change Model, the Leadership Identity Development Model, and the Student Leadership Model.